Project management basics : how to manage your project with checklists - McBride, Melanie (Apress, 2016)
Learn step-by-step instructions for managing any project in a clean sequence of five classic phases--initiating, planning, executing, releasing, and closing. This book sets out clearly and engagingly which tasks need to be done and when, how, and why they need to be done. Each chapter on one of the five phases walks you through all the steps in that phase's workflow, which are laid out in a checklist attached to the chapter. The checklists are graphically supplemented by flow charts and swim lane diagrams. The master checklist serves as a map and tool for project managers to use in the real world to run projects and keep them on track. Senior project manager and PM mentor Melanie McBride understands the predicament of beginning and junior project managers: "You're at the edge of a tornado, bombarded by overly excited people offering you a Mission Impossible. Everywhere you look there are cool shiny things swirling around your head--the earnest coworker telling you to go agile, the software package promising a turnkey collaboration solution, the PMO with an arm-long list of required processes. So how do you avoid getting whacked in the head by that airborne Mac truck of a customer commit? Oh, and what exactly do you need to do to get those flying monkeys to shut up?" Project Management Basics slips the spinning project manager into the eye of the storm where things are quiet and it's easy to figure out what to do next using the author's detailed checklists and hard-headed advice. She shows that project management doesn't have to be "a chaotic hot mess, leaving you with an egg-beater hairdo." With McBride's book and checklists in hand, even first-time project managers can pull off controlled, flying-monkey--free projects. What You Will Learn " The essential duties of a project manager " The project management lifecycle in five phases " The what, when, how, and why of PM tasks presented in detailed steps " How to leverage checklists for optimum efficiency and throughput " How to adapt workflow controls to low-PM organizations " How to enhance PM with vogue methodologies without obscuring the basics Who This Book Is For This book is for beginning and junior project managers seeking a concise, authoritative guide to the basics of project management, together with checklists, flow charts, and swim lane diagrams for immediate use in real-world projects